BS EN 60061. Lamp caps and holders together with gauges for the control of interchangeability and safety. Revision of 7004-21A-3 for E26, 7004-24A-2 for E39 and 7004-26-3 for E17. (2nd July 2021) - British Standards Institution,
No abstract available